PERENCANAAN PENANGANAN LANJUT BERDASARKAN ANALISIS KERUSAKAN AREA PARKIR PENUMPANG TERMINAL PENUMPANG BANDAR UDARA DJALALUDDIN-GORONTALO DENGAN METODE PAVEMENT CONDITION INDEX (PCI) ASTM D6433-07 - Agustin, Wahyu Shesar; Winiasri, Linda (Jurnal Penelitian, 2024)
The passenger parking area of the passenger terminal is one of the land side facilities that has an important role in the safety and comfort of passengers. The condition of the passenger parking area needs to ensure the feasibility of the pavement so as not to interfere with passenger activities. In maintaining the feasibility of pavement, advanced handling planning is required. Advanced handling planning must be adjusted to the needs of handling damage that occurs. Pavement Condition Index (PCI) is one of the methods commonly used in analyzing pavement damage. Through the results of the PCI can be determined maintenance planning and appropriate handling for damage to the passenger parking area. The method used is visual observation of Pavement Condition Index (PCI) based on ASTM D6433-07. The result of this research is that the passenger parking area of the Djalaluddin Airport passenger terminal gets a PCI value of 77.03. Damage that occurs includes: lowering the lane / shoulder, longitudinal cracks, holes, and weathering and loose grains. Based on KP 94 of 2015, the damage to the lane / shoulder is required to spread the material according to specifications and replace the material in the damage area. In light longitudinal crack damage, filling cracks with hotmix asphalt is required. For moderate and severe longitudinal cracking, additional treatment in the form of patching is required. Pothole damage requires patching and filling with hot mix asphalt. For minor weathering and raveling grain damage, only cleaning of the damaged area is required. In moderate weathering and raveling grain damage, patching and filling with hotmix asphalt are required. In severe weathering and raveling grain damage, an overlay with prior treatment is required.